2020
DOI: 10.1002/kin.21463
|View full text |Cite
|
Sign up to set email alerts
|

Isopropanol dehydration reaction rate kinetics measurement using H2O time histories

Abstract: H 2 O formation during thermal decomposition of isopropanol was measured behind reflected shock waves at temperatures ranging from 1127 to 1621 K at an average pressure of 1.42 atm using a laser absorption technique. Of the five modern chemical kinetics models used to compare the H 2 O time histories, the model from Li et al (Combust. Flame 2019;207:171-185) showed the best overall agreement. Sensitivity and rate of production analyses using the Li et al model (as well as those from AramcoMech 3.0, CRECK, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…None of the species show significant sensitivity to pressure, which indicates pressure-dependent reactions important in the 2-propanol pyrolysis system are at the high-pressure limit at the conditions studied. As noted earlier, this is consistent with the work by Cooper et al 19 who found, for the H 2 O elimination reaction, (R1a) was in the high-pressure limit for P > 1.4 atm. All the stable intermediate species measured in the current work were also observed in the propanol isomer pyrolysis study by Li et al 25 Their flow reactor study covered a broad range of temperatures and nearly 2 orders of magnitude of pressures.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…None of the species show significant sensitivity to pressure, which indicates pressure-dependent reactions important in the 2-propanol pyrolysis system are at the high-pressure limit at the conditions studied. As noted earlier, this is consistent with the work by Cooper et al 19 who found, for the H 2 O elimination reaction, (R1a) was in the high-pressure limit for P > 1.4 atm. All the stable intermediate species measured in the current work were also observed in the propanol isomer pyrolysis study by Li et al 25 Their flow reactor study covered a broad range of temperatures and nearly 2 orders of magnitude of pressures.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…Even more recently, Cooper et al 19 used shock tube studies and laser absorption to measure H 2 O production during 2propanol pyrolysis at a pressure of 1.42 atm and in the temperature range of 1127−1621 K. The authors found the data agreed well with the reaction mechanism created by Li et al 13 and that 2-propanol consumption was dominated by the dehydration channel (R1a) at the conditions studied. Because the water elimination channel was well-isolated in the study, Cooper et al 19 combined their results with the data from Heyne et al 17 and provided a further updated recommendation for the rate coefficient of the dehydration reaction that was in good agreement with measurements from 976 to 1621 K. Notably, Cooper et al 19 determined the dehydration reaction was within the high-pressure limit for pressures at and above 1.4 atm.…”
Section: ■ Introductionmentioning
confidence: 76%
See 3 more Smart Citations